Double-Digit Growth / How Great Companies Achieve It - No Matter What - Treacy Michael (Penguin Books, 2003)
A very useful book about managing for business growth. Why is it so Hard to Grow, Who's Achieving Double-Digit Growth, First Data Masters the Disciplines of Growth, The First Discipline: Keep the Growth You Have Already Earned, The Second Discipline: Take Business from Your5 Competitors, The Third Discipline: Show Up Where Growth Is Going to Happen, The Fourth Discipline: Invade Adjacent Markets, The Fifth Discipline: Invest in New Lines of Business, Manage Your Portfolio for Double-Digit Growth, Index.